How to avoid the marriage mart - Shepherd, Eva (Harlequin historicals., 2020)
At a weekend shooting party, where the guests are as determined to bag a marriage partner as they are a pheasant, two attendees are under siege. The Duke of Kingsford from a clutch of desperate debutantes, and Charlotte FitzRoy from her matchmaking mother! A pretend courtship between them should keep the others at bay, but an unexpected, impassioned kiss may just bring about the marriage they both sought to avoid!